Recent advances in plant science - (:unkn) unknown (Nova Science Publishers, Inc., 2020)
This book compiles original and review advances from a number of different focuses and latest developments in the important field of plant biology/science from around the world. The publication will be a beneficial and valuable resource for many people and groups related to plant growth and development as well as teachers, researchers, commercial growers and advanced students of plant biological science. The proposed publication can be used in some interesting and unusual places such as biofuels, edible vaccine, phytoremediation and cosmetics. © 2020 Nova Science Publishers, Inc. All rights reserved.